Unequal Access Of Immigrant Women To Reproductive Health Care In Madrid - Bravo, Ana (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This article is based on a study that deals with how gender and ethnicity as well as other factors such as socio-economic background and legal status in Spain may influence the unequal access of immigrant women to reproductive health care in Madrid. This article also examines immigrant women’s views on the Spanish reproductive health service and native health professionals when dealing with patients who are culturally and linguistically different from them.
Keywords: reproductive health; ethinicity; gender; migration